Odmiana medialna - WOJTAK, MARIA (Stylistyka, 2025)
In Polish stylistics, the linguistic variety associated with the media, initially limited to the press, was described using the terms style, language, or discourse. The choice of terminology depended on the prevailing cognitive perspective within stylistic research. Descriptions framed in terms of style (particularly journalistic style) tended to emphasise the connections between media language and other functional styles – artistic, colloquial, and official – thereby suggesting a lack of clearly distinctive features. Over time, however, Stanisław Gajda’s influential proposal to conceptualise media language as a stylistic melting pot gained widespread acceptance. The term media language (or language in the media) initially implied a focus on linguistic correctness in media discourse. Gradually, however, it came to encompass the study of communication practices specific to individual media platforms. This shift marked a transition toward a discursive research perspective. Strictly stylistic approaches may be either differential or descriptive. The melting pot metaphor highlights the chaotic blending of diverse stylistic elements. The descriptive approach, by contrast, situates style at a lower level of concretisation, linking it to the categories of discourse and genre. It acknowledges the antinomic nature of stylistic features and the open-ended repertoire of linguistic markers, focusing not on the origin of linguistic means, but on their communicative function.